(untitled) (Andamios, Revista de Investigación Social, 2014)
This article reviews the evolution in the treatment of prostitution’s lexicon in the Real Academia’s Diccionario de la Lengua Española (DRAE). The aim is to identify the presence of subjective features in academic lexicographical work, particularly if the new edition prepared for the end of 2014 (twenty-third edition) retains ideological elements detected in the 2001 edition (twenty-second edition). This study explores the macro- (list of headwords) and the microstructure (definitions and register marks) from discourse analysis and it verifies the low number of improvements have been made to reduce this subjectivity.